Effect of Tin Electrode (Sn), Electrode Distance and Thin Layer Size of Zinc Phthalocyanine (ZnPc) to Resistance Changes With Ozone Exposure - Agustina Mogi; Masruroh Masruroh; Rachmat Triandi Tjahjanto (Chemistry Department, The University of Brawijaya, 2018)
This study was aimed to determine the effect of tin electrode distances and the thickness of a thin layer of ZnPc (Zinc phtyalocyanine) toward changes in resistance with ozone exposure. Tin deposition on the glass surface was conducted using spraying method. The reaction between ozone and ZnPc produces electrical properties that can be read through the resistance value of the multimeter. Based on this study, it was investigated that the smaller a distance between the electrode and the thicker deposition of ZnPc lead to the less resistance. This showed that a thin layer of the conductivity increases along with the longer exposure to ozone gas. The movement of electrons with the hole was free.